Synthesis of Template-Free ZSM-5 Catalysis for Cyclohexene Hydration - Wang, Baohe; He, Jinxue; Chen, Shuang; Zhu, Jing; Sun, Hao (Asian Journal of Chemistry, 2015)
Template-free ZSM-5 zeolites were synthesized in the tetraethyl orthosilicate, sodium metasilicate and silica sol systems, respectively. Moreover, detailed analysis on the two different synthesis routes with sodium metasilicate as silica source were carried out. Catalytic performance in the cyclohexene hydration reaction was also investigated. The crystallinity, particle size, surface area and acidity varied of products were characterized by X-ray powder diffraction, scanning electron microscope, nitrogen adsorption, Fourier transform infrared spectroscopy, temperature-programmed desorption of ammonia (NH3-TRD) and thermogravimetric. Remarkable performance in the cyclohexene hydration reaction can be attained by using Na2SiO3 as silica source. It was shown that the improved Na2SiO3 synthesis route is the most suitable for synthesis of ZSM-5 catalysts.